Medication overuse headache - Ashina, Sait; Terwindt, Gisela M.; Steiner, Timothy J.; Lee, Mi Ji; Porreca, Frank; Tassorelli, Cristina; Schwedt, Todd J.; Jensen, Rigmor H.; Diener, Hans-Christoph; Lipton, Richard B. (Nature reviews. Disease primers, 2023)
Medication overuse headache (MOH) is a secondary headache disorder attributed to overuse of acute headache medications by a person with an underlying headache disorder, usually migraine or tension-type headache. MOH is common among individuals with 15 or more headache days per month. Although MOH is associated with substantial disability and reductions in quality of life, this condition is often under-recognized. As MOH is both preventable and treatable, it warrants greater attention and awareness. The diagnosis of MOH is based on the history and an unremarkable neurological examination, and is made according to the diagnostic criteria of the International Classification of Headache Disorders third edition (ICHD-3). Pathophysiological mechanisms of MOH include altered descending pain modulation, central sensitization and biobehavioural factors. Treatment of MOH includes the use of headache preventive therapies, but essential to success is eliminating the cause, by reducing the frequency of use of acute headache medication, and perhaps withdrawing the overused medication altogether. Appropriate treatment is usually highly effective, leading to reduced headache burden and acute medication consumption. Medication overuse headache is a secondary headache disorder that occurs in those with a primary headache disorder (commonly tension-type headache or migraine). This Primer reviews the epidemiology, pathophysiology, diagnosis and treatment of medication overuse headache, and discusses how this disorder affects the quality of life of patients.